Racemoramus panicula Calder 2012, comb. nov. - Calder, Dale R. (Zenodo, 2012)
Racemoramus panicula (G.O. Sars, 1874), comb. nov. Fig. 24 Campanulina panicula G.O. Sars, 1874: 121, pl. 5, figs. 9–13.— Kramp, 1941: 4, fig. 5.— Rees & Rowe 1969: 17.— Jägerskiöld, 1971: 61.— Cornelius, 1995a: 192, fig. 43D. Type locality. Norway: Oslofjord, 50–60 fm (91–110 m) (G.O. Sars 1874: 121). Museum material. Kosterhavet, 58°53.093’N, 11°05.668’E, 20–30 m, 09.ix.2010, biological dredge, R / V Nereus , two colonies or colony fragments, each with many hydrocauli, up to 3.8 cm high, on polychaete tubes and ascidians, without gonophores, ROMIZ B3916. Remarks. Kramp (1941) provided a thorough description of Opercularella panicula (G.O. Sars, 1874) based on specimens from Norway and Sweden, and remarked on its similarity to Campanulina denticulata Clarke, 1907 from deep waters of the eastern tropical Pacific (Clarke 1907) and Sagami Bay, Japan (Stechow 1913). Leloup (1974) discounted seeming differences between the two as ecologically induced and regarded them as conspecific. Vervoort (1966) referred Campanulina indivisa Fraser, 1948, from bathyal depths off California, to the synonymy of O. denticulata . Subsequent authors have mostly agreed that these are all synonyms. Nevertheless, their combined range is so extensive that it raises doubts whether a single species is represented. In addition to records in the eastern Atlantic (e.g., Cornelius 1995a, as Campanulina panicula ), similar hydroids have been reported from deep waters in the western Pacific (Stechow 1913: as Campanulina denticulata Hirohito 1995: as Opercularella panicula Schuchert 2003: as Campanulina panicula ), the eastern Pacific (Clarke 1907: as Campanulina denticulata Fraser 1948: as Campanulina (?) indivisa Leloup 1974: as Opercularella panicula ), and the Indian Ocean (Vervoort 1966: as? Opercularella denticulata ). Schuchert (2003) reported that materials from Indonesia were indistinguishable from those examined earlier from Iceland (Schuchert 2001a), supporting the hypothesis that a single species is represented. Its bathymetric range is also reported as being astoundingly wide, from 20–30 m (this study) to 5200 m (Stechow 1913, as Campanulina denticulata ). As noted above, I prefer on zoogeographic grounds to keep the Atlantic R. panicula distinct from the Indo-Pacific R. denticulata . This hydroid seems to be quite frequent in the Oslofjord, its type locality, having been collected at 12 stations there by Christiansen (1972). Records of R. panicula from Swedish waters are all from the Skagerrak (see Checklist). It was not recorded in Danish waters by Kramp (1935b). Of five figures of the species in the paper by Kramp (1941), only one (Fig. 5) was based on material from Sweden. Reported distribution. West coast of Sweden.—Säcken Reef (Rees & Rowe 1969, as Campanulina panicula ) to Skagerrak off Grebbestad (Kramp 1941, as Campanulina panicula ). Elsewhere.—Northeast Atlantic from Trondheimfjord, Norway (Storm 1882, as Campanulina panicula ), and Iceland (Schuchert 2000, 2001a, as Campanulina panicula ), to Morocco and southern Africa (Ramil & Iglesias 1988, as Opercularella panicula Cornelius 1995a, as Campanulina panicula ). : Published as part of Calder, Dale R., 2012, On a collection of hydroids (Cnidaria, Hydrozoa, Hydroidolina) from the west coast of Sweden, with a checklist of species from the region 3171, pp. 1-77 in Zootaxa 3171 (1) on page 26, DOI: 10.11646/zootaxa.3171.1.1, http://zenodo.org/record/5247704 : {"references": ["Sars, G. O. (1874) Bidrag til kundskaben om norges hydroider. Forhandlinger i Videnskabs-Selskabet i Christiania, 1873, 91 - 150.", "Kramp, P. L. (1941) Notes on the hydroid Campanulina panicula G. O. Sars. Goteborgs Kungliga Vetenskaps- och Vitterhets- Samhalles Handlingar, sjatte foljden, Series B, 1 (2), 1 - 11.", "Rees, W. J. & Rowe, M. (1969) Hydroids of the Swedish west coast. Acta Regiae Societatis Scientiarum et Litterarum Gothobergensis, Zoologica, 3: 1 - 23.", "Jagerskiold, L. A. (1971) A survey of the marine benthonic macro-fauna along the Swedish west coast 1921 - 1938. Acta Regiae Societatis Scientiarum et Litterarum Gothobergensis, Zoologica, 6, 1 - 146.", "Cornelius, P. F. S. (1995 a) North-west European thecate hydroids and their medusae. Part 1. Introduction, Laodiceidae to Haleciidae. Synopses of the British Fauna, n. s., 50, 347 pp.", "Clarke, S. F. (1907) Reports on the scientific results of the expedition to the eastern tropical Pacific, in charge of Alexander Agassiz, by the U. S. Fish Commission steamer \" Albatross, \" from October, 1904, to March, 1905, Lieut. - Commander L. M. Garrett, U. S. N., commanding. VIII. The hydroids. Memoirs of the Museum of Comparative Zoology at Harvard College, 35 (1), 1 - 18.", "Stechow, E. (1913) Hydroidpolypen der japanischen Ostkuste. II. Teil: Campanularidae, Halecidae, Lafoeidae, Campanulinidae und Sertularidae, nebst Erganzungen zu den Athecata und Plumularidae. Abhandlungen der Mathematisch-Physikalischen Klasse der Koniglichen Bayerischen Akademie der Wissenschaften, 3, Supplement-Band 2, 1 - 162.", "Leloup, E. (1974) Hydropolypes calyptoblastiques du Chili. Report No. 48 of the Lund University Chile Expedition 1948 - 1949. Sarsia, 55, 1 - 61.", "Vervoort, W. (1966) Bathyal and abyssal hydroids. Galathea Report, 8, 97 - 174.", "Fraser, C. M. (1948) Hydroids of the Allan Hancock Pacific Expeditions since March, 1938. Allan Hancock Pacific Expeditions, 4 (5), 179 - 343.", "Hirohito, The Showa Emperor (1995) The hydroids of Sagami Bay. Part II. Thecata. Biological Laboratory, Imperial House- hold, Tokyo, Japan, 355 pp.", "Schuchert, P. (2003) Hydroids (Cnidaria, Hydrozoa) of the Danish expedition to the Kei Islands. Steenstrupia, 27, 137 - 256.", "Schuchert, P. (2001 a) Hydroids of Greenland and Iceland (Cnidaria, Hydrozoa). Meddelelser om Gronland, Bioscience, 53, 1 - 184.", "Christiansen, B. O. (1972) The hydroid fauna of the Oslo Fiord in Norway. Norwegian Journal of Zoology, 20, 279 - 310.", "Kramp, P. L. (1935 b) Polypdyr (Coelenterata) I. Ferskvandspolypper og goplepolypper. Danmarks Fauna, 41, 1 - 207.", "Storm, V. (1882) Bidrag til kundskab om Throndhjemsfjordens fauna. IV. Om de i fjorden forekomme hydroide zoophyter. Kongelige Norske Videnskabers Selskabs Skrifter, 1881, 1 - 24.", "Schuchert, P. (2000) Hydrozoa (Cnidaria) of Iceland collected by the BIOICE programme. Sarsia, 85, 411 - 438.", "Ramil, F., & Iglesias, A. (1988) Sobre la presencia de Opercularella panicula (Sars, 1873) (Cnidaria: Hydroida) en las costas de la Peninsula Iberica. Thalassas, 6, 79 - 82."]}